Pembelajaran Matematika dengan Model Search, Solve, Create and Share (SSCS) di MAN 1 Muara Labuh - Eliza, Rivdya; Aulia, Fitri (Math Educa Journal, 2017)
The purpose of this research are: 1) to know the learning activity of learners mathematics which is taught by Search, Solve, Create, and Share (SSCS), and 2) model to know the ability of problem solving of mathematics learners who taught by SSCS learning model in the class XI MIA MAN 1 Muara Labuh academic year 2016/2017. This research belongs to a kind of quasi-experimental research with randomized control group only design. In this study design, a group of subjects taken from a particular population were randomly assigned into two groups, the experimental group and the control group. After analyzing the data, it is known that the learning activity of the students after applying the SSCS learning model has improved towards the better from the first meeting to the fifth meeting, ie 35%, 45%, 55%, 68%, 77%. Based on the hypothesis test obtained ttable = 1.645 and tcount = 2.598 so obtained (2.598> 1.645) at 95% confidence interval. Because tcount > ttable then hypothesis in this research accepted. Thus, students 'math-problem-solving skills taught by SSCS learning models are higher than the students' uneducated mathematical problem-solving skills with SSCS learning modelsKeywords: Problem solving abilities, search, solve, sreate and share (SSCS) learning models